Method for preparing super-ductile prestressed filling material from modified CFB fly ash and application thereof

CN122831648APending Publication Date: 2026-09-29SHANXI LUQIAO DEV & CONSTR CO LTD +3
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611281251.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

[0004]本发明针对现有CFB飞灰资源化利用中无法兼顾高工作性、高强度、高体积稳定性的技术瓶颈,提供一种改性CFB飞灰制备超延性预应力填筑料的方法,本发明正是要利用CFB飞灰“有害”的体积膨胀特性,将其转化为“有益”的膨胀应力源,化害为利

Benefits of technology

(1)本发明颠覆了传统CFB飞灰资源化利用中试图消除其膨胀性的技术偏见,化害为利,利用CFB飞灰自身高硫、高铝的化学特性,将其作为生成预应力的核心源,开发出一种具备自预应力功能的超延性填筑料,为CFB飞灰的大规模、高附加值资源化利用开辟了全新路径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122831648A_ABST
    Figure CN122831648A_ABST
Patent Text Reader

Abstract

The present application relates to solid waste resource utilization and special engineering material technical field, specifically relates to a kind of modified CFB fly ash preparation super ductility prestressed filling material method and application;The method of the present application is first pretreated to CFB fly ash, by mechanical grinding and coating modifier, reduce its water absorption and improve its activity, again with slag powder, floating bead, gypsum powder, aluminate cement clinker, dispersing agent proportioning mixed evenly to make composite cementing powder;Subsequently modified CFB fly ash-based cementing powder and polypropylene emulsion, chopped fiber, water are mixed evenly, and high fluidity slurry is prepared;After pouring, the filling body with expansion stress and high ductility is formed.The present application solves the engineering performance deterioration problem caused by high water absorption and high sulfur content of CFB fly ash, turns harm into benefit, and converts it into super ductility filling material with self-prestressed function, realizes large-scale, high value-added resource utilization of CFB fly ash.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste resource utilization and special engineering materials technology, specifically to a method and application of preparing ultra-ductile prestressed filler material from modified CFB fly ash. Background Technology

[0002] Circulating fluidized bed combustion technology is widely used for low-calorific-value coal and coal gangue due to its high combustion efficiency and low desulfurization cost. However, the associated byproduct—circulating fluidized bed fly ash (CFB fly ash)—has a huge annual emission volume, and its resource utilization is a challenge for the industry. Compared with ordinary pulverized coal boiler fly ash, CFB fly ash particles are extremely fine, and due to its low combustion temperature (850-900℃), it contains a large amount of amorphous metakaolinite (active Al2O3) and free CaO, giving it pozzolanic activity. However, its high f-CaO and anhydrite (CaSO4) content results in extremely high water demand during hydration, poor workability, and continuous formation of ettringite after hardening, causing volume expansion and cracking. This makes it impossible to guarantee the safety of concrete incorporating CFB fly ash, severely limiting its application in the building materials field.

[0003] Patent CN119822707A discloses a method for preparing ultra-early-strength micro-expansion roadbed grouting material using CFB fly ash. This method utilizes the expansion effect during the hydration process of CFB fly ash to suppress the shrinkage problem of cement and geopolymer grouting materials. However, CFB fly ash has a high water absorption rate. If undisturbed CFB fly ash is used directly, the high water absorption rate leads to the addition of large amounts of water to achieve workability, forming a porous and loose matrix. This not only results in low strength but also causes the expansion effect in the later stages of hydration to directly crack rigid materials such as geopolymers and cement. Therefore, it is necessary to systematically modify CFB fly ash to prepare a new type of fill material that combines high flowability, self-compacting properties, high ductility, and the ability to generate prestress, in order to meet the special requirements of backfilling projects for sealing, density, and crack resistance. Summary of the Invention

[0004] This invention addresses the technical bottleneck in the current utilization of CFB fly ash resources, which cannot simultaneously achieve high workability, high strength, and high volume stability. It provides a method for preparing ultra-ductile prestressed filler material using modified CFB fly ash. This invention aims to utilize the "harmful" volume expansion characteristics of CFB fly ash to transform it into a "beneficial" source of expansion stress, turning harm into benefit.

[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: a method for preparing ultra-ductile prestressed fill material by modifying CFB fly ash, comprising the following steps: S1. CFB fly ash and modifier are added to a ball mill and mixed to perform surface modification treatment to obtain modified CFB fly ash with a particle size of <32μm. S2. The modified CFB fly ash obtained in step S1 is mixed with slag powder, cenospheres, gypsum powder, aluminate cement clinker and dispersant in proportion to obtain a composite cementitious powder with high hydration activity. S3. The composite cementitious powder obtained in step S2 is mixed evenly with soil and stone materials, polypropylene emulsion, chopped fibers and water in a mixing device to prepare a highly fluid slurry, which is the ultra-ductile prestressed fill material.

[0006] As a further limitation of the technical solution of the present invention, in step S1, the CFB fly ash is fly ash produced by calcining low-quality coal in a circulating fluidized bed boiler, and its chemical composition includes: Al2O3: 18~32wt.%, SiO2: 30~50wt.%, CaO: 8~20wt.%, SO3: 6~15wt.%, and loss on ignition <8wt.%.

[0007] As a further limitation of the technical solution of the present invention, in step S1, the modifier is a composite of at least two of the following: titanate coupling agent, calcium stearate, and hydrogen-containing silicone oil emulsion; the amount of modifier added is 0.1% to 2% of the mass of CFB fly ash. The CFB fly ash and the modifier are ball-milled together, integrating ultrafine grinding and surface modification. Mechanical force is used to destroy the capillary pores of the original particles, while the modifier forms an effective hydrophobic layer on the surface of the newly formed particles. This fundamentally solves the problem of high water absorption caused by the well-developed micropores of CFB fly ash, ensuring that the subsequent slurry still has good workability at a low water-binder ratio. Furthermore, the modifier can also enhance the interfacial compatibility between CFB fly ash and polypropylene emulsion and chopped fibers, and improve the deformability of the matrix.

[0008] As a further limitation of the technical solution of the present invention, in step S2, the addition amounts of slag powder, cenospheres, gypsum powder, and aluminate cement clinker are 20wt.%~80wt.%, 0wt.%~20wt.%, 1wt.%~30wt.%, and 5wt.%~30wt.%, respectively, based on the mass of CFB fly ash; the addition amount of dispersant is 0.05wt.%~0.5wt.%, based on the total mass of all powders (the powders are composed of modified CFB fly ash, slag powder, cenospheres, gypsum powder, and aluminate cement clinker).

[0009] As a further limitation of the technical solution of the present invention, in step S2, the dispersant is at least one of sodium tripolyphosphate, diethylene glycol and sodium polyacrylate.

[0010] The core design of this invention's gelling powder lies in constructing a multi-source, synergistic hydration-expansion system: slag micropowder provides potential hydraulic properties, ensuring continuous strength growth in the later stages; aluminate cement clinker provides early strength and active aluminum phase; gypsum powder supplements sulfate; and the two, together with CFB fly ash, precisely control the ratio of effective SO3 to active Al2O3 in the system, laying the chemical basis for generating an appropriate amount of ettringite expansion stress; cenospheres, as lightweight, high-strength spherical glass microspheres, fill the spaces between particles, improving rheology and reducing matrix brittleness; the dispersant not only ensures the uniform dispersion of the multi-component powder in the slurry, but also the Ca of sodium tripolyphosphate... 2+ The complexation process effectively avoids the impact of excessive free calcium in CFB fly ash on the initial hydration reaction.

[0011] As a further limitation of the technical solution of the present invention, in step S3, the soil and rock material is one or more of sand, crushed stone, recycled aggregate from construction waste, and tailings, and the particle size meets the following requirements: 20% to 50% of particles are 1 to 10 mm, 30% to 80% are <0.1 mm, and the remaining particles have a particle size of 0.1 to 10 mm. The ratio of the composite cementitious powder to the soil and stone is 1:1 to 1:10; the amount of polypropylene emulsion added is 0.5% to 10% of the mass of the composite cementitious powder. The chopped fiber is made by mixing polyvinyl alcohol fiber with at least one plant regenerated fiber such as sisal fiber and bamboo fiber in a mass ratio of 1:1. The length of the chopped fiber is 5~50mm, and the amount of chopped fiber added is 0.1%~2.0% of the total mass of composite cementitious powder and soil and stone materials.

[0012] This invention forms a dense skeleton through a strictly designed soil and rock gradation, and a three-dimensional elastic network is formed in the hardened slurry by polypropylene emulsion. The organic-inorganic fibers of mixed lengths work together to bridge micro-cracks and macro-cracks, giving the material extremely high ductility and crack resistance, which is sufficient to accommodate the volume expansion caused by the formation of ettringite, and convert the expansion into compressive stress that is beneficial to the matrix, thus achieving an overall "self-prestressed" effect.

[0013] As a further limitation of the technical solution of the present invention, in step S3, the amount of water added is determined by controlling the flow spread of the slurry between 220mm and 260mm to ensure its good self-leveling and self-compacting properties.

[0014] In addition, the present invention also provides the application of the ultra-ductile prestressed fill material prepared by the above method in backfilling projects.

[0015] Furthermore, the ultra-ductile prestressed fill material is pumped or poured into the area to be filled. After solidification and hardening, it is covered and cured for 28 days to form a fill body with expansion stress and high ductility.

[0016] Furthermore, the compressive strength at 28 days is 1.0–18.0 MPa, the flexural strength is 0.1–3.0 MPa, the ultimate compressive strain is 1%–10%, the lateral confined expansion stress ranges from 0.02–0.80 MPa, and the linear free expansion is 1–30 mm / m. This material combines the ductility of metals with the compressive strength of cement-based materials, making it a novel inorganic-organic composite prestressed functional filling material.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention overturns the technical bias of trying to eliminate the expansion of CFB fly ash in the traditional resource utilization of CFB fly ash, turns harm into benefit, utilizes the high sulfur and high aluminum chemical properties of CFB fly ash itself as the core source of prestressing, and develops a super-ductile filler with self-prestressing function, opening up a new path for the large-scale, high-value-added resource utilization of CFB fly ash.

[0018] (2) This invention systematically solves the contradiction between workability, strength and volume stability caused by the high water absorption and high expansion of CFB fly ash through multiple technologies such as ball milling hydrophobic integrated modification, multi-source hydration-expansion system design, and toughening of short-cut fibers and polymer (polypropylene emulsion), and achieves the material design goal of "self-leveling, self-compacting, self-prestressing and ultra-ductility".

[0019] (3) By introducing aluminate cement clinker and gypsum powder, the present invention forms a gradient of reaction rate with SO3 and active Al2O3 in CFB fly ash, making the formation rate and amount of ettringite controllable. Different expansion stress levels can be designed according to engineering requirements, thus realizing the controllability of expansion performance.

[0020] (4) The present invention uses polyvinyl alcohol fiber and plant regenerated fiber to synergistically toughen the material at different scales. Combined with the polymer network of polypropylene emulsion, the ultimate compressive strain of the material can reach 1%~10%, which fundamentally overcomes the problem that brittle inorganic cementitious materials are prone to cracking under expansion stress.

[0021] (5) This invention makes extensive use of industrial and agricultural wastes such as CFB fly ash, slag, recycled aggregates from construction waste, and plant fibers, which is in line with the concept of green, low-carbon and circular development and has significant economic and environmental benefits. Attached Figure Description

[0022] Figure 1 The figures show the compressive stress-strain curves of the samples in Examples 1-5.

[0023] Figure 2 The image shows the compression failure morphology of the sample prepared in Example 1.

[0024] Figure 3A is a bending failure test diagram of the sample prepared in Example 1. Figure 3 B is a cross-sectional morphology diagram of the sample prepared in Example 1.

[0025] Figure 4 This is a graph showing the free expansion rate test of the sample in Example 1.

[0026] Figure 5 A is a diagram showing the on-site pouring process of the fill material in Example 1. Figure 5 B is a diagram showing the on-site pouring effect of the fill material in Example 1. Detailed Implementation

[0027] The present invention will be described in more detail below with reference to the embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.

[0028] A method for preparing ultra-ductile prestressed fill material from modified CFB fly ash includes the following steps: S1. CFB fly ash and modifier are added to a ball mill and mixed to perform surface modification treatment to obtain modified CFB fly ash with a particle size of <32μm. S2. The modified CFB fly ash obtained in step S1 is mixed with slag powder, cenospheres, gypsum powder, aluminate cement clinker and dispersant in proportion to obtain a composite cementitious powder with high hydration activity. S3. The composite cementitious powder obtained in step S2 is mixed evenly with soil and stone materials, polypropylene emulsion, chopped fibers and water in a mixing device to prepare a highly fluid slurry, which is the ultra-ductile prestressed fill material.

[0029] In different embodiments, the amount of modifier added in step S1 is 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, or 2% of the mass of CFB fly ash.

[0030] In different embodiments, in step S2, the amount of slag powder added is 20 wt.%, 30 wt.%, 40 wt.%, 50 wt.%, 60 wt.%, 70 wt.%, or 80 wt.% of the mass of CFB fly ash; or the amount added is within the range defined by any two of the aforementioned example values, such as 20 wt.%-30 wt.%, 20 wt.%-40 wt.%, 40-70 wt.%, or 60 wt.%-80 wt.%.

[0031] The amounts of cenospheres added were 0 wt.%, 5 wt.%, 15 wt.%, and 20 wt.% of the CFB fly ash mass, respectively.

[0032] The amount of gypsum powder added is 1 wt.%, 3 wt.%, 5 wt.%, 7 wt.%, 9 wt.%, 11 wt.%, 13 wt.%, 15 wt.%, 17 wt.%, 19 wt.%, 21 wt.%, 23 wt.%, 25 wt.%, 27 wt.%, 29 wt.%, or 30 wt.% of the mass of CFB fly ash; or the amount added is within the range defined by any two of the aforementioned example values, such as 1 wt.-3 wt.%, 3 wt.%-7 wt.%, 11 wt.-17 wt.%, or 15 wt.%-30 wt.%.

[0033] The amount of aluminate cement clinker added is 5 wt.%, 10 wt.%, 15 wt.%, 20 wt.%, 25 wt.%, and 30 wt.% of the mass of CFB fly ash; or the amount added within the range defined by any two of the aforementioned example values, such as 5 wt.%-10 wt.%, 5 wt.%-15 wt.%, and 15 wt.%-25 wt.%.

[0034] The amount of dispersant added is 0.05 wt.%, 0.10 wt.%, 0.15 wt.%, 0.20 wt.%, 0.25 wt.%, 0.30 wt.%, 0.35 wt.%, 0.40 wt.%, 0.45 wt.%, and 0.5 wt.% of the total mass of all powders.

[0035] In different embodiments, in step S3, the ratio of the composite cementitious powder to the soil and stone is 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, or 1:10; and the amount of polypropylene emulsion added is 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, or 10% of the mass of the composite cementitious powder.

[0036] The chopped fibers are made by mixing polyvinyl alcohol fibers with at least one plant regenerated fiber such as sisal fiber and bamboo fiber in a mass ratio of 1:1. The fiber lengths are 5mm, 10mm, 15mm, 20mm, 25mm, 30mm, 35mm, 40mm, 45mm, and 50mm. The amount of chopped fibers added is 0.1%, 0.5%, 1.0%, 1.5%, and 2.0% of the total mass of composite cementitious powder and soil and stone materials, respectively.

[0037] In the following examples and comparative examples, the chemical composition of CFB fly ash and the particle size distribution of iron tailings, manufactured sand, and recycled fine aggregate are shown in Tables 1 and 2.

[0038] Table 1. Chemical composition (wt.%) of the original CFB fly ash used in Examples 1-5 and Comparative Examples 1-3

[0039] Table 2. Particle size distribution of iron tailings, manufactured sand, and recycled fine aggregate used in the examples.

[0040] Example 1 A method for preparing ultra-ductile prestressed fill material from modified CFB fly ash includes the following steps: S1. Take 100 kg of CFB fly ash, add 1.5 kg of composite modifier (composed of titanate coupling agent and calcium stearate in a mass ratio of 1:1), and grind them together in a ball mill for 60 min to obtain modified CFB fly ash with a median particle size of about 25 μm.

[0041] S2, take 100 kg of modified CFB fly ash obtained in step S1, and mix it with 50 kg of S95 grade slag powder, 10 kg of cenospheres, 15 kg of desulfurized gypsum powder, 15 kg of CA50 aluminate cement clinker, and 0.2 kg of dispersant (sodium tripolyphosphate) in a mixer for 5 min to obtain composite cementitious powder A.

[0042] S3, take 100kg of composite cementitious powder A, 400kg of mixed soil and rock material (composed of manufactured sand and iron tailings in a mass ratio of 1:1), 3kg of polypropylene emulsion, 1kg of short chopped fiber (composed of polyvinyl alcohol fiber and sisal fiber in a 1:1 ratio, with fiber length of 15~25mm) and an appropriate amount of water and put them into a mixer. Stir until the flow expansion reaches 240mm±10mm to obtain slurry.

[0043] The obtained slurry is poured into a mold coated with a release agent, the surface is covered with a film to keep it moist, the mold is removed after 24 hours, and the film is continued to be covered for curing for 28 days.

[0044] The 28-day performance test results of the filler material prepared in this embodiment are as follows: compressive strength 8.48 MPa, flexural strength 1.22 MPa, ultimate compressive strain 4.96%. Figure 1 As shown, the lateral confined expansion stress is 0.48 MPa, and the linear free expansion is 15.2 mm / m. The results indicate that the material exhibits significant ductility and moderate expansion prestress while maintaining high compressive strength.

[0045] Figure 2 The figure shows the compression failure morphology of the sample prepared in Example 1. As can be seen from the figure, the ultra-ductile prestressed filler prepared in this invention not only has high strength, but also can withstand large deformation during compression failure, and remains "cracked but not broken" after crack penetration, without overall collapse, demonstrating good toughness characteristics.

[0046] Figure 3Figure A shows the bending failure test of the sample prepared in Example 1, and Figure B shows the cross-sectional morphology of the sample prepared in Example 1. As can be seen from the figures, even though the crack has completely penetrated the sample after bending failure, the sample as a whole has not broken. After manual peeling, a large number of uniformly dispersed polyvinyl alcohol fibers and sisal fibers can be seen at the fracture surface, which is the basis for the good volume stability of this material.

[0047] Figure 4 This is a graph showing the free expansion rate test of the sample in Example 1. As can be seen from the dial gauge values ​​in the graph, the cast samples all exhibit expansion under natural conditions.

[0048] Figure 5 Figure A shows the on-site pouring process of the filler material in Example 1, and Figure B shows the on-site pouring effect of the filler material in Example 1. As can be seen from the figures, the filler material prepared with the formula proposed in this invention has good fluidity and can self-level and self-compact.

[0049] Example 2 The only difference between this embodiment and Embodiment 1 is that: In step S2, the proportions of each powder are adjusted to obtain higher prestress. The specific proportions for S2 are as follows: 100 kg of modified CFB fly ash is mixed evenly with 40 kg of S95 grade slag powder, 0 kg of cenospheres, 30 kg of desulfurized gypsum powder, 30 kg of CA50 aluminate cement clinker, and 0.3 kg of dispersant (diethylene glycol) to obtain composite cementitious powder B.

[0050] In step S3, the amount of composite cementitious powder B is 100 kg, the amount of soil and stone is 300 kg (particle composition is the same as in Example 1), the amount of polypropylene emulsion is 4 kg, and the amount of chopped fiber is 2 kg (polyvinyl alcohol fiber and sisal fiber are mixed in a 1:1 ratio, and the fiber length is 15~25 mm). The flow spread is controlled at 220 mm by adjusting the amount of water.

[0051] The 28-day performance test results of the filler material prepared in this embodiment are as follows: compressive strength 3.66 MPa, flexural strength 0.53 MPa, ultimate compressive strain 7.62%. Figure 1 As shown, the lateral confined expansion stress is 0.78 MPa, and the linear free expansion is 18 mm / m. This material is suitable for backfilling loose strata requiring a high expansion compaction effect.

[0052] Example 3 The only difference between this embodiment and Embodiment 1 is that: In step S3, the toughening effect of the polymer and fibers is enhanced to obtain ultra-high ductility. The specific ratio for S3 is as follows: take 100 kg of composite cementitious powder A, mix it with 200 kg of mixed soil and stone (particle composition as in Example 1), 8 kg of polypropylene emulsion, and 3 kg of chopped fibers (polyvinyl alcohol fiber and sisal fiber mixed in a 1:1 ratio, fiber length 30~50 mm). The flow spread is controlled at 250 mm by adjusting the amount of water.

[0053] The 28-day performance test results of the filler material prepared in this embodiment are as follows: compressive strength 2.63 MPa, flexural strength 0.92 MPa, ultimate compressive strain 9.44%. Figure 1 As shown; the lateral confined expansion stress is 0.25 MPa, and the linear free expansion is 26 mm / m. This mix has an ultimate compressive strain close to 10%, high flexural strength, and exhibits ultra-high ductility similar to metals, making it suitable for flexible connection parts with extremely high requirements for resistance to deformation and cracking.

[0054] Example 4 The only difference between this embodiment and Embodiment 1 is that: In step S1, the modifier is composed of calcium stearate and hydrogen-containing silicone oil emulsion in a mass ratio of 1:1, and the amount added is 2.0% of the mass of CFB fly ash. In step S3, the soil and rock material is composed of recycled fine aggregate from construction waste and iron tailings in a mass ratio of 1:2, and the plant fiber in the chopped fiber is bamboo fiber. The remaining steps and proportions are the same as in Example 1.

[0055] The 28-day performance test results of the filler material prepared in this embodiment are as follows: compressive strength 7.95 MPa, flexural strength 0.86 MPa, ultimate compressive strain 4.60%. Figure 1 As shown, the lateral confined expansion stress is 0.45 MPa, and the linear free expansion is 8.5 mm / m. This indicates that high-performance filler materials can be obtained by using different combinations of hydrophobic modifiers and recycled aggregates from construction waste.

[0056] Example 5 The only difference between this embodiment and Embodiment 1 is that: In step S3, 100 kg of composite cementitious powder A is mixed with 100 kg of soil and rock material. The soil and rock material consists of manufactured sand and iron tailings in a mass ratio of 3:1. The proportion of particles with a diameter of 1-10 mm is increased to 50%, the proportion of particles smaller than 0.1 mm is reduced to 30%, and the remaining particles have a diameter of 0.1-10 mm. The amount of polypropylene emulsion used is 5 kg, and the amount of chopped fiber added is reduced to 0.5 kg. The flow spread is controlled at 260 mm by adjusting the amount of water used.

[0057] The 28-day performance test results of the filler material prepared in this embodiment are as follows: compressive strength 14.29 MPa, flexural strength 1.92 MPa, ultimate compressive strain 2.65%. Figure 1 As shown, the lateral confined expansion stress is 0.55 MPa, and the linear free expansion is 18 mm / m. This mix design exhibits high strength and moderate ductility, making it suitable for backfill projects with certain load-bearing requirements.

[0058] Comparative Example 1 (Unmodified CFB fly ash) The difference between this comparative example and Example 1 is that no modifier is added in step S1, and the original CFB fly ash is ground separately to the same fineness.

[0059] Results: To achieve the same 240mm flow spread, the water-cement ratio needed to be significantly increased from 0.38 in Example 1 to 0.52. The 28-day compressive strength was only 3.12 MPa, the flexural strength was 0.28 MPa, and the ultimate compressive strain was 2.31%. Figure 1 As shown, significant volume shrinkage occurred, microcracks appeared on the surface of the specimen, and the effective expansion stress could not be measured. This indicates that without hydrophobic modification, the high water absorption of CFB fly ash leads to a loose and porous matrix, which not only significantly reduces strength but also fails to effectively transfer expansion stress, thus inducing drying shrinkage cracking.

[0060] Comparative Example 2 (without added chopped fibers) The difference between this comparative example and Example 1 is as follows: No chopped fibers were added in step S3, and the remaining raw materials and preparation process were the same as in Example 1.

[0061] Results: During the later stages of curing, due to expansion stress, obvious macroscopic cracks appeared on the surface of the specimen, exhibiting a brittle splitting failure mode. The 28-day compressive strength was 5.50 MPa, and the ultimate compressive strain was only 0.55%. Figure 1 As shown, the bending failure strength is 0.15 MPa. This proves that chopped fibers are the key component for realizing the transformation of materials from "expansion cracking" to "ultraductance prestress". Without the bridging and toughening effect of fibers, the matrix cannot accommodate the volume expansion caused by ettringite.

[0062] Comparative Example 3 (without added aluminate cement clinker and gypsum powder) The difference between this comparative example and Example 1 is that in step S2, an equal amount of slag powder is used to replace aluminate cement clinker and desulfurized gypsum powder (i.e., the amount of slag powder is increased to 80 kg, and the amount of aluminate cement clinker and gypsum powder is 0 kg). The remaining raw materials and preparation process are the same as in Example 1.

[0063] Results: The 28-day confined expansion stress was only 0.05 MPa, the linear free expansion was 1.2 mm / m, the compressive failure strength was 6.80 MPa, and the ultimate compressive strain was 5.52%. Figure 1 As shown, this indicates that relying solely on the mineral composition of CFB fly ash, the rate and amount of ettringite formation are insufficient to generate effective prestress within 28 days. The introduction of aluminate cement clinker and gypsum powder is a key technical means to provide sufficient active aluminum phase and sulfate, regulate the expansion process, and realize the preparation of prestressed filler.

[0064] The above description is merely a preferred embodiment of the present invention and is illustrative rather than restrictive. Those skilled in the art will understand that many changes, modifications, and even equivalents can be made within the spirit and scope defined by the claims of the present invention, all of which will fall within the protection scope of the present invention.

Claims

1. A method for preparing ultra-ductile prestressed fill material from modified CFB fly ash, characterized in that, Includes the following steps: S1. CFB fly ash and modifier are added to a ball mill and mixed to perform surface modification treatment to obtain modified CFB fly ash with a particle size of <32μm. S2. The modified CFB fly ash obtained in step S1 is mixed evenly with slag powder, cenospheres, gypsum powder, aluminate cement clinker and dispersant in proportion to obtain composite cementitious powder. S3. The composite cementitious powder obtained in step S2 is mixed evenly with soil and stone materials, polypropylene emulsion, chopped fibers and water in a mixing device to prepare a slurry, which is the ultra-ductile prestressed fill material.

2. The method for preparing ultra-ductile prestressed fill material from modified CFB fly ash according to claim 1, characterized in that, In step S1, the CFB fly ash is fly ash produced by calcining low-quality coal in a circulating fluidized bed boiler, and its chemical composition includes: Al2O3: 18~32wt.%, SiO2: 30~50wt.%, CaO: 8~20wt.%, SO3: 6~15wt.%, and loss on ignition <8wt.%.

3. The method for preparing ultra-ductile prestressed fill material from modified CFB fly ash according to claim 1, characterized in that, In step S1, the modifier is composed of at least two of the following: titanate coupling agent, calcium stearate, and hydrogen-containing silicone oil emulsion; the amount of modifier added is 0.1% to 2% of the mass of CFB fly ash.

4. The method for preparing ultra-ductile prestressed fill material from modified CFB fly ash according to claim 1, characterized in that, In step S2, the amounts of slag powder, cenospheres, gypsum powder, and aluminate cement clinker added are 20wt.%~80wt.%, 0wt.%~20wt.%, 1wt.%~30wt.%, and 5wt.%~30wt.% of the mass of CFB fly ash, respectively; the amount of dispersant added is 0.05wt.%~0.5wt.% of the total mass of all powders.

5. The method for preparing ultra-ductile prestressed fill material from modified CFB fly ash according to claim 1, characterized in that, In step S2, the dispersant is at least one of sodium tripolyphosphate, diethylene glycol, and sodium polyacrylate.

6. The method for preparing ultra-ductile prestressed fill material from modified CFB fly ash according to claim 1, characterized in that, In step S3, the soil and rock material is one or more of sand, crushed stone, recycled aggregate from construction waste, and tailings, and the particle size meets the following requirements: 1~10mm accounts for 20%~50%, <0.1mm accounts for 30%~80%, and the remaining particles have a particle size of 0.1~10mm. The ratio of the composite cementitious powder to the soil and stone is 1:1 to 1:10; the amount of polypropylene emulsion added is 0.5% to 10% of the mass of the composite cementitious powder. The chopped fiber is made by mixing polyvinyl alcohol fiber with at least one plant regenerated fiber such as sisal fiber and bamboo fiber in a mass ratio of 1:

1. The length of the chopped fiber is 5~50mm, and the amount of chopped fiber added is 0.1%~2.0% of the total mass of composite cementitious powder and soil and stone materials.

7. The method for preparing ultra-ductile prestressed fill material from modified CFB fly ash according to claim 1, characterized in that, In step S3, the amount of water added is determined by controlling the flow spread of the slurry between 220mm and 260mm.

8. The application of the ultra-ductile prestressed fill material prepared by the method according to any one of claims 1-7 in backfilling projects.

9. The application according to claim 8, characterized in that, The ultra-ductile prestressed fill material is pumped or poured into the area to be filled. After solidification and hardening, it is covered and cured for 28 days to form a fill body with expansion stress and high ductility.

10. The application according to claim 8, characterized in that, The compressive failure strength at 28 days is 1.0~18.0MPa, the flexural failure strength is 0.1~3.0MPa, the ultimate compressive strain is 1%~10%, the lateral confined expansion stress range is 0.02~0.80MPa, and the linear free expansion is 1~30mm / m.

Citation Information

Patent Citations

  • Method for preparing super-early-strength micro-expansion roadbed grouting material from CFB ash

    CN119822707A